Proteome-wide analysis of lysine β-hydroxybutyrylation in the myocardium of diabetic rat model with cardiomyopathy - Luo, Weiguang; He, Mei; Luo, Qizhi; Li, Yi (Frontiers in Cardiovascular Medicine, 2023)
Lysine ß-hydroxybutyrylation (kbhb), a novel modification of lysine residues with the ß-hydroxybuty group, is associated with ketone metabolism in numerous species. However, its potential role in diabetes, especially in diabetic cardiomyopathy (DCM), remains largely unexplored. In this study, using affinity enrichment and liquid chromatography-mass spectrometry (LC-MS/MS) method, we quantitatively analyze the kbhb residues on heart tissues of a DCM model rat. A total of 3,520 kbhb sites in 1,089 proteins were identified in this study. Further analysis showed that 336 kbhb sites in 143 proteins were differentially expressed between the heart tissues of DCM and wild-type rats. Among them, 284 kbhb sites in 96 proteins were upregulated, while 52 kbhb sites in 47 proteins were downregulated. Bioinformatic analysis of the proteomic results revealed that these kbhb-modified proteins were widely distributed in various components and involved in a wide range of cellular functions and biological processes (BPs). Functional analysis showed that the kbhb-modified proteins were involved in the tricarboxylic acid cycle, oxidative phosphorylation, and propanoate metabolism. Our findings demonstrated how kbhb is related to many metabolic pathways and is mainly involved in energy metabolism. These results provide the first global investigation of the kbhb profile in DCM progression and can be an essential resource to explore DCM’s pathogenesis further.